(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Financial performance indicators, especially the analysis of financial ratios, have become very important information to support the decisions of departments and investors alike to assess financial stability and the growth of economic units. Therefore, this research focuses on using financial ratios to analyze the annual financial reports of economic units, to find out the extent of growth and stability of the economic unit during a time series. The results of the performance evaluation process for the research sample (the National Company for Agricultural Production) showed that the process of analyzing the financial ratios is very useful for users of the financial statements to make a decision about the extent of the financial stability of the economic units and to know whether the economic unit has used the available resources effectively